2014
DOI: 10.1186/1476-4598-13-163
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the roles of CD44 and lipolysis stimulated lipoprotein receptor in conveying Clostridium perfringens iota toxin cytotoxicity in breast cancer

Abstract: BackgroundTranslational exploration of bacterial toxins has come to the forefront of research given their potential as a chemotherapeutic tool. Studies in select tissues have demonstrated that Clostridium perfringens iota toxin binds to CD44 and lipolysis stimulated lipoprotein receptor (LSR) cell-surface proteins. We recently demonstrated that LSR expression correlates with estrogen receptor positive breast cancers and that LSR signaling directs aggressive, tumor-initiating cell behaviors. Herein, we identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
(95 reference statements)
1
15
0
Order By: Relevance
“…Together with our previous functional studies in breast cancer cell lines (1, 2), the current data support LSR as a novel transcriptional regulator that is responsive to microenvironmental cues. LSR is capable of nuclear localization and DNA binding, and its nuclear functions may be associated with poor patient outcome.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Together with our previous functional studies in breast cancer cell lines (1, 2), the current data support LSR as a novel transcriptional regulator that is responsive to microenvironmental cues. LSR is capable of nuclear localization and DNA binding, and its nuclear functions may be associated with poor patient outcome.…”
Section: Discussionsupporting
confidence: 85%
“…Immunofluorescence was performed with appropriate controls as described (1, 2, 25). Anti-LSR antibodies; Atlas Antibodies and Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CDT is a binary toxin that has an enzymatic subunit, CDTa (47.4 kDa), with ribosyltransferase activity, and a pore-forming delivery subunit, termed CDTb (99 kDa) (15,(19)(20)(21)(22)(23). Prior to cellular entry via endosomes (24)(25)(26)(27), CDT associates with host cell receptor(s), such as the lipolysisstimulated lipoprotein receptor (LSR) and/or CD44 (28)(29)(30)(31). Based on studies with other binary toxins, it was suggested that the low pH in endosomes triggers CDTa translocation into the cytoplasm, via the cell-binding and pore-forming entity, CDTb, but a detailed molecular mechanism for this process remains unknown (32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%